Exploring hybrid models for universal access to basic solar energy services in informal settlements: Case studies from South Africa and Zimbabwe. (October 2019) - Conway, Damian; Robinson, Blake; Mudimu, Patience; Chitekwe, Tawanda; Koranteng, Kweku; Swilling, Mark
Abstract: In order to achieve Sustainable Development Goal 7 (SDG 7), innovative approaches will be required to deliver affordable, reliable, sustainable and modern energy to Africa's poor. As a partial contributor to this goal, Solar Home Systems (SHSs) are an increasingly affordable and reliable option for low-income, informal settlement, urban households to initially access electricity (for at least lighting and media) in a manner that bypasses the legal, financial and practical barriers that often impede grid electrification. Other authors have argued for adaptive hybrid models for delivering and scaling access to SHS so that synergies between government- donor- or market-led approaches can be harnessed to achieve truly universal, and thus equitable, access. We look at two case studies of SHS delivery models that could, if combined, embody some of the envisaged benefits of the hybrid idea. The first case study is a social enterprise in South Africa that operates as a subsidised fee-for-service solar electricity utility. The emphasis is on efficient operating systems combined with local job creation, which together help to minimise running costs and thus maximise end-user affordability and produce wider local economic benefits. The second case study, in Zimbabwe, uses well-established social processes and women-led savings groups to build strong organisational capacity and accountability within the community. This establishes a robust social contract and a resilient mechanism for technical delivery and grass-roots information flow. The respective strengths and weakness of these two models appear to dovetail in a way that supports the case for a combination of the two approaches in a partnership with a shared core mission of advancing SDG 7 for under-served residents of informal settlements in Sub-Saharan Africa.